Evaluation of soil management systems for viticulture - Dal Bó, Marco Antonio; Becker, Mauro (Pesquisa Agropecuaria Brasileira, 1994)
An experiment was carried out to evaluate the effect of different soil management systems on grapevine yield and quality. The treatments were as follows: green covering of soil with vetch (Vicia sativa L.) during the entire vegetative cycle; desiccated vetch by herbicide at the beginning of grapevine bud break; a band of native vegetation in the inter-row space and clean soil. The treatments with vetch and native vegetation during grapevine vegetative period, decreased grape yield in the tested conditions. Desiccated vetch with herbicide at beginning of grapevine bud break eliminated the competition effect and increased yield compared to clean soil.